Attempt at Analysis of the Poem Radix, Matrix by Paul Celan - STEPANYAN, SERGEY (Bulletin of Yerevan University B: Philology, 2021)
The present article aims to illustrate the poetological experience of Paul Celan (the poem "Radix, Matrix"), a Jew poet, who keeps writing poems in German, his mother tongue (other language). Ideological absolutism of German makes the unique absurdity basis for every non-German being. The fundamental concepts and words of this language are changed and recharged.